2011
DOI: 10.1080/13607863.2011.562179
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy for managing dementia may protect against burden and depression in Alzheimer's caregivers

Abstract: Further longitudinal investigation is warranted to determine if self-efficacy might be usefully considered a target in future interventional studies to alleviate symptoms of burden and depression in Alzheimer's caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 46 publications
4
111
2
1
Order By: Relevance
“…We can suppose that the clinical symptoms of dementia are possibly not perceived as uncontrollable by the caregivers assessed in this study. Gallagher et al 29 have shown that high self-efficacy in dementia caregivers could mitigate the symptoms of burden and depression. In addition, caregivers with an internal locus of control, regarding the person with dementia's behavior, would be less susceptible to the negative consequences caused by stress 30 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We can suppose that the clinical symptoms of dementia are possibly not perceived as uncontrollable by the caregivers assessed in this study. Gallagher et al 29 have shown that high self-efficacy in dementia caregivers could mitigate the symptoms of burden and depression. In addition, caregivers with an internal locus of control, regarding the person with dementia's behavior, would be less susceptible to the negative consequences caused by stress 30 .…”
mentioning
confidence: 99%
“…The presence of burden depends on a series of subjective factors 29 . We can suppose that the clinical symptoms of dementia are possibly not perceived as uncontrollable by the caregivers assessed in this study.…”
mentioning
confidence: 99%
“…The CRSES scored moderately at the quality assessment stage, and no further validation studies were identified. Whilst there is a wealth of research measuring self-efficacy for caregivers of people with dementia [49], there appears to be a lack of research concerning self-efficacy for people with dementia. This may be due to an absence of specific measures, developed for this population.…”
Section: Resultsmentioning
confidence: 99%
“…Also, elderly female caregivers report more suffering and clinical symptoms. This symptomatology has been evaluated as frequent among caregivers in different studies [8,21,22].…”
Section: Discussionmentioning
confidence: 99%